(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: The study presents the life and work of Ferenc Boncz, the actuality having been marked by the erection of a statue in his honour in his birthplace. Methodology: The present study is based on the contemporary news reports, articles, professional writings and the publications of Ferenc Boncz, and was primarily prepared using the methodological tools of legal history research. Findings: Ferenc Boncz studied theology, fought in the 1848–49 War of Independence, and later graduated as a lawyer. From 1877 he was head of the Royal Administration of Public Foundations, with the rank of ministerial advisor. He was primarily concerned with public funds and church policy, and was a recognised ecclesiastical lawyer of his time, publishing numerous books and studies. In recognition of his services, he was awarded the Knight’s Cross of the Order of Lipót on his retirement. Value: The activity and work of Ferenc Boncz in the service of his country and the public is considered outstanding, and its presentation serves as an example even today.